Opening web applications for third-party development: a service-oriented solution. Issue 4 (December 2016) - Kerdoudi, Mohamed; Tibermacine, Chouki; Sadou, Salah
Abstract Web applications are nowadays prevalent software systems in our everyday's life. A lot of these applications have been developed for end users only. Thus, they are not designed by considering future extensions that would be developed by third parties. One possible and interesting solution for opening these applications for such kind of extension development is to create and deploy Web services starting from these applications. In this paper, we present a method and a tool for semiautomatically creating Web service implementations from applications having Web interfaces. The proposed method generates operations that are published in Web services for each functionality provided by a Web application. In addition, it generates new operations starting from Web interfaces. Our approach goes further in the creation of services by generating executable orchestrations, as BPEL processes, starting from navigations in the Web interfaces of these applications and by providing BPMN choreography specifications starting from the collaborations between the generated Web services. We implemented and experimented our solution in the migration of three real-world Web applications toward Web service-oriented systems.